ROLE OF MAGNETIC RESONANCE IMAGING IN NODAL AND METASTATIC STAGING OF PROSTATE CANCER: A SYSTEMATIC REVIEW AND META-ANALYSIS - Hafizar; Rahman, Fakhri; Rumanter, Rainier; Hamid, Agus Rizal Ardy Hariandy; Mochtar, Chaidir Arif; Umbas, Rainy; Matondang, Sahat BRE (Indonesian Urological Association, 2022)
Objective: To evaluate the usage of MRI in prostate cancer staging, especially in nodal involvement (N-staging) and metastasis (M-staging) of prostate cancer. Methods: This is a systematic review and meta-analysis assessing role of MRI in nodal and metastasis staging of prostate cancer. Search of studies were done through search engine using Pubmed, Cochrane, and EBSCO Host and manual searching. Quality of eligible studies were assessed using a revised version of Quality Assessment of Diagnostic Accuracy Studies (QUADAS-2) and analyzed in pooled analysis according to nodal involvement or metastasis staging, modality of diagnosis used as the index test and gold standard used using STATA version 13. Results: Total 26 studies corresponding with study’s eligibility criteria were found. Overall, usage of MRI has a sensitivity of 47% (95% CI 35% - 60%; I2 83.08%) and a specificity of 93% (95% CI 89% - 96%, I2 82.21%) in nodal involvement staging of prostate cancer, while using of MRI in M-staging of prostate cancer shows a sensitivity of 94% (95% CI 86% - 97%) and a specificity of 99% (95% CI 97% - 99%). Using lymphotrophic superparamagnetic nanoparticle (LSN) - enhanced MRI gives higher sensitivity than using MRI without LSN for N-staging of prostate cancer. Conclusion: The usage of MRI in prostate cancer staging has a moderate sensitivity and relatively high specificity in detecting lymph node. Moreover, it plays an important role and even can be used as a modality of choice in assisting bone metastatic prostate cancer detection.